Antibiotics for acute cough: an international observational study of patient adherence in primary care. - Francis, N; Gillespie, D; Nuttall, J; Hood, K; Little, P; Verheij, T; Coenen, S; Cals, J; Goossens, H; Butler, C (2012)
BACKGROUND: Non-adherence to acute antibiotic prescriptions is poorly described and may impact on clinical outcomes, healthcare costs, and interpretation of research. It also results in leftover antibiotics that could be used inappropriately. AIM: To describe adherence to antibiotics prescribed for adults presenting with acute cough in primary care, factors associated with non-adherence, and associated recovery. DESIGN AND SETTING: Prospective observational cohort study in general practices in 14 European primary care networks. METHOD: GPs recorded patient characteristics and prescribing decisions for adults with acute cough or clinical presentation suggestive of lower respiratory tract infection. Patients recorded antibiotic consumption and daily symptoms over 28 days. Rates of adherence to prescribed antibiotics were assessed, and factors associated with non-adherence were identified using logistic regression. Recovery was compared using a Cox proportional hazards model. RESULTS: Of 2520 patients prescribed immediate or no antibiotics at the index consultation, 282 (11.2%) took an antibiotic during the follow-up period that was not prescribed for them at the index consultation. Of these, 38.1% had no reconsultations during this period. Prior duration of symptoms, antibiotic treatment duration, antibiotic choice, and primary care network were all associated with adherence. There was no difference in time to recovery between those who were prescribed antibiotics at the index consultation and were fully adherent, partially adherent, and non-adherent. CONCLUSION: Non-adherence to antibiotics for acute cough or lower respiratory tract infection is common. Duration of treatment, choice of antibiotic, and setting were associated with adherence but adherence to treatment was not associated with differences in recovery.